2004
DOI: 10.1016/j.brainres.2004.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of α1, α4, γ2, and δ subunits of GABAA receptors in hippocampal granule cells

Abstract: GABA A receptors are pentamers composed of subunits derived from the α, β, γ, δ, θ, ε, and π gene families. α1, α4, γ2, and δ subunits are expressed in the dentate gyrus of the hippocampus, but their subcellular distribution has not been described. Hippocampal sections were double-labeled for the α1, α4, γ2, and δ subunits and GAD65 or gephyrin, and their subcellular distribution on dentate granule cells was studied by means of confocal laser scanning microscopy (CLSM). The synaptic versus extrasynaptic locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
116
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(128 citation statements)
references
References 37 publications
11
116
0
1
Order By: Relevance
“…The subunit composition determines the pharmacological properties of GABA A R. Drugs, including neurosteroids, which interact with the receptors, can affect the subunit mRNA expression (Sun et al, 2004). GABA A R usually contains two a-subunits, two b-subunits, and either a g or d-subunit, with the d-subunit being rare (Sun et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subunit composition determines the pharmacological properties of GABA A R. Drugs, including neurosteroids, which interact with the receptors, can affect the subunit mRNA expression (Sun et al, 2004). GABA A R usually contains two a-subunits, two b-subunits, and either a g or d-subunit, with the d-subunit being rare (Sun et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The subunit composition determines the pharmacological properties of GABA A R. Drugs, including neurosteroids, which interact with the receptors, can affect the subunit mRNA expression (Sun et al, 2004). GABA A R usually contains two a-subunits, two b-subunits, and either a g or d-subunit, with the d-subunit being rare (Sun et al, 2004). GABA A Rs containing a d-subunit, rather than a g-subunit, are more sensitive to neurosteroids (Belelli et al, 2002), and mice lacking GABA A d-subunits are less sensitive to neurosteroids (Brown et al, 2002;Mihalek et al, 1999Mihalek et al, , 2001Stell et al, 2003;Wohlfarth et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…GABA A receptors are composed of six α subunits, four β subunits, three types of γ subunits and one of each δ, θ, ε and π subunits (Macdonald and Botzolakis 2009).GABRA4 is the human promoter for the α4 subunit (Roberts, Raol et al 2005). The dentate granule cells in the hippocampus show high expression of α4 GABA A subunit receptors (Sun, Sieghart et al 2004). Studies have shown that α4 subunit expression increases in the dentate gyrus of epileptic rats .…”
Section: Discussionmentioning
confidence: 99%
“…In order to package all our chosen genes within that size limit, promoters are required which are both small and neuronal-specific. GABRA4 is the human promoter of GABA A α4 receptors (Sun, Sieghart et al 2004). …”
Section: Gabra4 Promotermentioning
confidence: 99%
See 1 more Smart Citation